Emergence and characterization of IncFII/IncR plasmids with multiple 5,692 bp- blaKPC−2-bearing tandem repeats in ceftazidime/avibactam non-susceptible Klebsiella pneumoniae strains - Liu, Hongmao; Zhu, Mei; Lu, Junwan; Wu, Shan; Ye, Rujian; Pan, Wei; Li, Yirong; Bao, Qiyu; Huang, Dawei (Frontiers in Microbiology, 2025)
Ceftazidime/avibactam (CAZ/AVI) is widely recognized as an effective treatment for infections caused by KPC-producing Klebsiella pneumoniae (KPC-Kp). However, the prevalence of CAZ/AVI resistance among KPC-Kp isolates has increased rapidly in recent years. In this study, high-level carbapenem resistance and enhanced CAZ/AVI resistance were observed in two hypervirulent carbapenem-resistant K. pneumoniae isolates, KP1878 and KP3034, following prolonged carbapenem use. Virulence phenotypes were confirmed using the string test and a Galleria mellonella larvae infection model. Real-time quantitative PCR revealed that the relative expression of blaKPC−2 in KP1878 and KP3034 was 2.4-fold and 11.6-fold higher, respectively, than that in the CAZ/AVI-susceptible KPC-Kp strain KP1880. Whole-genome sequencing showed that the blaKPC−2 gene resided within an identical 5,692-bp ΔklcA-korC-ΔISKpn6-blaKPC−2-ISKpn8-ΔtnpR-IS26 tandem repeat, which was replicated twice and four times in plasmids pKPC1878 and pKPC3034, respectively. Compared with KP1880, the β-lactamase hydrolysis activities of crude cell lysates derived from KP1878 and KP3034 were significantly higher in their ability to hydrolyze meropenem, ceftazidime, and nitrocefin. S1-nuclease-digested pulsed-field gel electrophoresis, along with Southern blot and restriction fragment length polymorphism fingerprinting, identified plasmid profiles but revealed one or more 5.6-kilobase variations in the regions hybridized with the KPC-specific probe. Further comparative genomic analysis suggested that a potential homologous recombination event occurred between the blaKPC−2-carrying plasmid and the pLVPK-like virulence plasmid of KP3034, leading to the generation of a cointegrated plasmid that combined both virulence and CAZ/AVI resistance.